Standardisation of synovial tissue infiltrate analysis: how far have we come? how much further do we need to go?. Issue 1 (23rd June 2005) - Smith, M D; Baeten, D; Ulfgren, A-K; McInnes, I B; Fitzgerald, O; Bresnihan, B; Tak, P P; Veale, D
Abstract : Changes in cellular infiltrate and expression of cytokines, chemokines, and cell adhesion molecules as a result of therapeutic interventions in rheumatoid arthritis can be demonstrated in the synovial membrane. However, before synovial tissue analysis can be used as an outcome measure in such studies, standardisation of the site and method of synovial tissue acquisition, methods of tissue processing, and appropriate methods of detection and measurement of cell lineage specific markers and relevant biological proteins is needed.